Konstruksi Berita Penyelidikan Kasus Suap Harun Masiku - Maman Abdurahman; Afriyah Erma Yanti (Communicative : Jurnal Dakwah dan Komunikasi, 2020)
In this analysis, the researcher uses the framing model from Pan and Kosiciki which is a modification of the operational dimensions of van Dijk's discourse analysis. The framing analysis model owned by Zhongdang Pan and Gerald M. Kosicki is considered to offer framing analysis with a more comprehensive coverage. This framing model studies at least the framing device divided into four major structures. First, syntactic structure; second, the script structure; third, the thematic structure; fourth, rhetorical structure. Using the framming analysis method, related to the news regarding the investigation into the harun masiku bribery case presented by the online media detik.com, the writer finds the conclusion that detik.com highlights certain aspects in constructing the incident. The aspect that is highlighted is regarding the people who are allegedly involved in the case where the PAW bribery is not traced, namely Harun Masiku. The online media detik.com only features one person, namely Yasonna Laoly as Minister of Law and Human Rights. Whereas in this case it was not only Yasonna who deserved suspicion, but also the Director General of Immigration and also people who were in the PAW bribery circle